The neuroprotective effect and RNA‐sequence analysis of postconditioning on the ischemic stroke with diabetes mellitus tree shrew model - Ling Zhao (Wiley, 2021)
Abstract Introduction Patients with comorbidity of ischemic stroke (IS) and diabetes mellitus (DM) show poor neurological functional recovery, and ischemic postconditioning (IPOC) should be considered a powerful neuroprotective method for IS. However, whether it should be introduced for patients with IS and DM remains controversial. This study established a DM with IS (DMIS) tree shrew model, which was intervened by IPOC to assess its neuroprotective effects and also to analyze the relevant mechanism by RNA‐sequence and bioinformatics analysis. Methods Fifty‐four tree shrews were randomly divided into a sham operation control group, a DMIS group, and an IPOC group (DMIS model), with 18 tree shrews per group. Triphenyl tetrazolium chloride (TTC), hematoxylin‐eosin (HE) staining, transmission electron microscopy (TEM), and RNA‐sequence analysis were performed to assess the IPOC effect. Results IPOC reduced infarct size and reduced nerve cell injury in IS tree shrews with DM. RNA‐seq analysis showed that IPOC significantly increased the expression of the homeobox protein SIX3, while downregulating the expression of HLA class II histocompatibility antigens DQ beta 1 chain, CAS1 domain‐containing protein 1, and cytokine receptor‐like factor 2. The most downregulated signaling pathways include the NF‐κB signaling pathway, TNF signaling pathway, and Fc gamma R‐mediated phagocytosis. Conclusions IPOCs have a neuroprotective effect in a DMIS animal model that reduces infarct size and nerve cell injury. This mechanism might be related to reducing inflammation and stress responses that decreases the activity of TNF and NF‐κB signaling pathways.